New Parents Experienced Lower Parenting Self-Efficacy during the COVID-19 Pandemic Lockdown - Anja Xue; Vivian Oros; Pearl La Marca-Ghaemmaghami; Felix Scholkmann; Franziska Righini-Grunder; Giancarlo Natalucci; Tanja Karen; Dirk Bassler; Tanja Restin (MDPI AG, 2021)
Background: The COVID-19 pandemic is a global issue which affects the entire population's mental health. This study evaluates how restrictions to curtail this pandemic change parenting self-efficacy, depressive symptoms, couple satisfaction and health-related quality of life in parents after delivery of a newborn. Methods: In this prospective single center evaluation of parental self-efficacy and quality of life, four validated questionnaires were used to repeatedly assess parenting self-efficacy (Tool to measure Parental Self-Efficacy, TOPSE), depressive symptoms (Edinburgh Postnatal Depression Scale, EPDS), couple satisfaction (Couple Satisfaction Index, CSI) and health-related quality of life (short form 12, SF12). Fifty-three parents of 50 infants answered a total number of 63 questionnaires during the lockdown period to limit the spread of COVID-19. These questionnaires were matched with 63 questionnaires of 58 other parents that had answered them before or after strong pandemic related measures. Results: Parents experienced lower parenting self-efficacy during the strict pandemic measures as compared to before and after (p = 0.04). In terms of age, socioeconomic, marital status and duration of hospitalization we detected no significant difference between both groups. On univariate linear regression, TOPSE scores were associated with gestational age (p = 0.044, parameter estimate: 1.67, 95% CI: 0.048 to 3.301), birth weight (p = 0.035, parameter estimate: 0.008, 95% CI: 0.001 to 0.015), number of newborns' siblings (p = 0.0554, parameter estimate: 7.49, 95% CI: −0.174 to 15.145) and distance of home from hospital (p = 0.043, parameter estimate: −0.38, 95% CI: −0.745 to −0.011). Interestingly, there was a positive correlation between quality of life and TOPSE scores, suggesting that those who experience a higher self-efficacy also have a higher quality of life. Conclusions: When implementing a lock-down period psychological effects such as lower experience of parental self-efficacy have to be considered.